2019
DOI: 10.1111/apt.15526
|View full text |Cite
|
Sign up to set email alerts
|

Faecal microbiota transplant decreases mortality in severe and fulminant Clostridioides difficile infection in critically ill patients

Abstract: Summary Background Severe and fulminant Clostridioides difficile infection is associated with high mortality rates. While faecal microbiota transplant has been shown to be effective for recurrent C difficile infection, there is little data on the utility of faecal microbiota transplant in severe or fulminant C difficile infection. Aim To compare the outcomes of antibiotics and faecal microbiota transplantation vs antibiotics alone (standard of care) in critically ill patients with severe or fulminant C diffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 26 publications
5
33
1
2
Order By: Relevance
“…Tixier et al have evaluated the use of FMT for patients with severe or fulminant CDI in a retrospective, matched cohort study of 48 hospitalised patients requiring admission to an intensive care unit . They identified 426 patients with severe or fulminant CDI who received critical care in their New York hospital.…”
supporting
confidence: 89%
“…Tixier et al have evaluated the use of FMT for patients with severe or fulminant CDI in a retrospective, matched cohort study of 48 hospitalised patients requiring admission to an intensive care unit . They identified 426 patients with severe or fulminant CDI who received critical care in their New York hospital.…”
supporting
confidence: 89%
“…[23][24][25] A recent study of FMT in this setting demonstrated that the number needed to treat with FMT to prevent one death was 3.2 relative to standard antibiotic therapy. 26 A lack of utilization of FMT, particularly in this context, is life threatening and of great concern. Almost half (46%) of physicians were concerned about disease transmission risk, and the majority of these concerns centered on infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…Severe or fulminant CDI carries a high mortality, reported to be between 36 and 58%, which is not mitigated by colectomy 23–25 . A recent study of FMT in this setting demonstrated that the number needed to treat with FMT to prevent one death was 3.2 relative to standard antibiotic therapy 26 . A lack of utilization of FMT, particularly in this context, is life threatening and of great concern.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies define “refractory” as “recurrent CDI after multiple treatment courses [ 18 , 19 ]”, which is more consistent with “recurrence”. Fulminant CDI is similarly difficult to study, because studies evaluating fulminant CDI usually defines the patient populations as “severe and fulminant”, including severe CDI (WBC count of ≥15,000 cells/mL or a serum creatinine of >1.5 mg/dL) as defined by IDSA guidelines, which can be quite broad [ 23 ]. The lack of accuracy in reporting or definition of cases makes the interpretation of data from FMTs studies even more difficult.…”
Section: Discussionmentioning
confidence: 99%